Visual preference evaluation on urban landmarks in the process of urbanization: a case study of Shanghai Oriental Pearl Radio & TV Tower. Issue 5 (3rd September 2021) - Zhao, Mengmeng; Zhang, Jian; Cai, Jun
ABSTRACT: In the context of China's fast urbanization, the background of urban landmarks is constantly changing, which provides useful examples for the study of visual preference evaluation of urban landmarks. With the Shanghai Oriental Pearl Radio & TV Tower as research object, the pictures of 24 years were used as the research material, and the height ratio, building density, distance, and volume of the surrounding buildings were set as the physical characteristics to be studied. Photo stimulation experiments were conducted with participants of different demographic characteristics, the results of which were analyzed accordingly. The analytical results indicate that the height ratio, building density, distance, volume of Oriental Pearl Radio & TV Tower's surrounding buildings are the main factors that influence people's visual preference evaluation; people of different demographic characteristics (gender, age, growth experience) pay different attention to the height ratio, building density, distance, volume, and render different emotional and aesthetic responses to the fast change of this urban landmark and its surroundings. This research provides a valuable reference to urban landmark design and the development strategy of urban planning.